Applying Dictologloss Technique on Students’ Narrative Text: A Quasi Experimental Study - Kholid, Mohammad Ridho; Abimanto, Dhanan; Pratiwi, Wiwied (CV. Creative Tugu Pena, 2020)
This article was to find out about the effectiveness of applying dictogloss technique on students’ narrative text. A Quasi-Experimental design was used in this method, with using pre-test and post test design. Subject of this research was at the eleventh grade at state senior high 10 Bandar Lampung. The result of this study showed that the value of to (tobservation ) was 5.2. The value of t table with degree of freedom 38 in significance degree 5 % was 2.02 and in significance degree 1% was 2.71. It indicated that to was higher than or 2.02 < 5.26 > 2.71. for those analysis, the null hypothesis (Ho) was rejected and t alternative hypothesis (Ha) was accepted. Hence, it was inferred that there were significant difference between students’ narrative writing score who were taught by dictoglos technique. Keywords: Dictogloss Technique, Experimental Design, Narrative Text